2020
DOI: 10.1002/glia.23958
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells instruct a beneficial phenotype in reactive astrocytes

Abstract: Transplanted mesenchymal stromal/stem cells (MSC) ameliorate the clinical course of experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), reducing inflammation and demyelination. These effects are mediated by instructive cross‐talk between MSC and immune and neural cells. Astroglial reaction to injury is a prominent feature of both EAE and MS. Astrocytes constitute a relevant target to control disease onset and progression and, based on their potential to acquire stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(124 reference statements)
1
6
0
Order By: Relevance
“…It has been demonstrated that among these secreted factors, IL-1α, TNF-α, and complement component 1, subcomponent q (C1q) are all required as initiators of neurotoxic A1 astrocytes induction in vivo , and that A1 astrocytes significantly decrease in number only when treated with the anti-inflammatory TGF-β or fibroblast growth factor (FGF) [ 95 ]. In light of this evidence, it can be hypothesized that the effect of MSCs is mediated by a possibly still unknown inducer of the protective A2 phenotype (see also [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that among these secreted factors, IL-1α, TNF-α, and complement component 1, subcomponent q (C1q) are all required as initiators of neurotoxic A1 astrocytes induction in vivo , and that A1 astrocytes significantly decrease in number only when treated with the anti-inflammatory TGF-β or fibroblast growth factor (FGF) [ 95 ]. In light of this evidence, it can be hypothesized that the effect of MSCs is mediated by a possibly still unknown inducer of the protective A2 phenotype (see also [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with MSCs, the massive microgliosis observed in the neocortex of EAE-affected mice appears to be effectively counteracted, featuring reduced cell hypertrophy, reduced IBA1 and Ccl2 /CCL2 expression, increased neuroprotective SALL1, and reduced NVU adjoining processes. Thus, microglia respond directly to MSC treatment, or indirectly, through resident cell effectors such as astrocytes that have been recently demonstrated to respond to MSC treatment, reacquiring stem cell properties and protective and reparative actions [ 30 ]. Direct modulation of the microglia phenotype by MSCs has been demonstrated in vitro in co-cultures of microglia and MSCs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MSC can “sense” the environment created by the signals emitted by injured tissues and home to target areas where they secrete an array of molecules, including cytokines/chemokines and neurotrophic factors 59 . MSC can even induce alterations in the secretion of certain factors in host cells through an orchestrated crosstalk 53,60 . Their paracrine mechanisms can be mediated through direct diffusion into the extracellular space or by material encapsulated in small vesicles.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…59 MSC can even induce alterations in the secretion of certain factors in host cells through an orchestrated crosstalk. 53,60 Their paracrine mechanisms can be mediated through direct diffusion into the extracellular space or by material encapsulated in small vesicles. These vesicles can contain signalling lipids, mRNAs, regulatory miRNAs or even small organelles, which may also support the survival/ recovery of host cells.…”
Section: Therapeutic Outcomes In Neurological Contextmentioning
confidence: 99%